Is gold a hedge or a safe-haven asset in the COVID–19 crisis? - Akhtaruzzaman, Md; Boubaker, Sabri; Lucey, Brian M.; Sensoy, Ahmet (Economic modelling, 2021)
This study examines the role of gold as a hedge or safe-haven asset in different phases of the COVID-19 pandemic crisis, corresponding to the timing of fiscal and monetary stimuli to support the weakened economy. Using high-frequency data, the results show that gold served as a safe-haven asset for stock markets during Phase I (December 31, 2019–March 16, 2020) of the pandemic. However, gold lost its safe-haven role during Phase II (March 17−April 24, 2020). The optimal weights of gold in S&P 500, Euro Stoxx 50, Nikkei 225, and WTI crude oil portfolios significantly increased during Phase II, suggesting that investors expanded investment in gold as a ‘flight-to-safety asset’ during the crisis. Further, hedging costs increased significantly during Phase II. These findings provide insight for individual and institutional investors and guidance to policymakers, regulators, and media on how gold evolved as a hedge and safe-haven asset in different phases of the pandemic. •We study the role of gold in the COVID–19 crisis.•Gold acts as safe haven asset during Phase I (31 Dec 2019–16 Mar 2020).•Gold loses the safe haven status during Phase II (17 Mar −24 April 2020).•Investors increase their investment in gold during Phase II as a ‘flight-to-safety asset’.•Hedging cost increases during Phase II.